Kajian Keanekaragaman Jenis Baccaurea spp., Pemanfaatan, Potensi dan Upaya Konservasinya di Kebun Raya Bogor - Esti Munawaroh; Inggit Puji Astuti (Journal of Tropical Ethnobiology, 2021)
Baccaurea is a genus of flowering plants belonging to the Phyllanthaceae family. This genus consists of approximately 43 species, these species are generally known as fruit-producing plants. As germplasm found growing in Indonesia, this genus is also part of the Bogor Botanical Gardens collection. The main duties and functions of the Botanical Gardens are conservation, research, education, tourism and environmental services. Research on the species of Baccaurea spp and its benefits in the Bogor Botanical Gardens is based on more than ten years of direct observation data of all members of the Baccaurea family in the garden, as well as data stored in the Registration Unit and plant collection catalog. This research aims to reveal its diversity, conservation and potential at the Bogor Botanical Gardens. Bogor Botanical Gardens were recorded to have collected 15 species of Baccaurea and 3 still sp., with 52 individual specimens, all of which were trees. Most of the collections are native to Indonesia, 92.30% (48 specimens) and only 4 specimens (7.70%) from abroad. Among the original Indonesian collections were dominated by plants from Sumatra 44.23% (23 specimens), Kalimanatan 26.92% (14 specimens), Java 7 specimens (13.46%), Maluku 3.84% (2 specimens) and Sulawesi 3,84% (2 specimens). Judging from the potential of these species, they can be developed as traditional medicinal plants (10 species), the source of foodstuffs are 15 species of fruit, 1 species of spice, 2species of beverage ingredient and 2 species of food mixture. As wood for buildings and household items (15 species), dyes (3 species). From the number of plants in the Baccaurea collection, it is recorded that there is an old collection plant that is over 75 years old, Baccaurea javanica Mull. Arg., Baccaurea racemosa (Reinw. Ex Bl) Mull. Arg., And Baccaurea reticulata Hook. F.